2021
DOI: 10.1016/j.puhe.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Sharp increase in depression and anxiety among Brazilian adults during the COVID-19 pandemic: findings from the PAMPA cohort

Abstract: Objectives We aimed to compare the prevalence of depression and anxiety symptoms before and during the pandemic and identify factors associated with aggravated mental health symptoms. Study design Retrospective cohort study. Methods We identified the proportion of normal, mild, moderate, and severe symptoms of depression and anxiety before and during the social distancing restrictions in adults from southern Brazil. An online, self-administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
2
28

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(148 citation statements)
references
References 38 publications
16
102
2
28
Order By: Relevance
“…Some of the psychological impacts of a pandemic might include the fear of getting sick or dying (Hall et al, 2008), the loss of a loved one (Hawryluck et al, 2005), the loss of income (Van Bortel et al, 2016) as well as decreasing satisfaction in life (Ammar et al, 2020) and well-being (Chtourou et al, 2020;Trabelsi et al, 2021) associated with the experience of social isolation. The lack of reliable and up-to-date information on the recovery cases and possible treatments can increase anxiety, stress (Wang et al, 2020), and depression symptoms (Hyland et al, 2020;Feter et al, 2021). Levels of uncertainty can be aggravated by inaccurate or misleading information about the outbreak in social media (Tang et al, 2018), a factor that has been recurrent in Brazil (Ribeiro and Leist, 2020).…”
Section: Covid-19 Outbreak and Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the psychological impacts of a pandemic might include the fear of getting sick or dying (Hall et al, 2008), the loss of a loved one (Hawryluck et al, 2005), the loss of income (Van Bortel et al, 2016) as well as decreasing satisfaction in life (Ammar et al, 2020) and well-being (Chtourou et al, 2020;Trabelsi et al, 2021) associated with the experience of social isolation. The lack of reliable and up-to-date information on the recovery cases and possible treatments can increase anxiety, stress (Wang et al, 2020), and depression symptoms (Hyland et al, 2020;Feter et al, 2021). Levels of uncertainty can be aggravated by inaccurate or misleading information about the outbreak in social media (Tang et al, 2018), a factor that has been recurrent in Brazil (Ribeiro and Leist, 2020).…”
Section: Covid-19 Outbreak and Mental Healthmentioning
confidence: 99%
“…Congruently, Goularte et al (2021), with a larger sample (N = 1996), identified that anxiety (81.9%) and depression (68%) were the most common psychological disorders found during the COVID-19 pandemic in Brazilian adults. Furthermore, the pandemic can worsen the condition of patients with pre-existing mental health diseases (Ho et al, 2020;Feter et al, 2021). Given this scenario, studies have demonstrated the effectiveness of Fullana et al (2020) and recommended activities to prevent or mitigate the impacts of confinement on mental health, such as music listening (Kar et al, 2020).…”
Section: Covid-19 Outbreak and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that outbreaks of diseases, such as COVID-19, can have a severe impact on the psychological health of people, and they may experience fear of contracting the disease, stigma, helplessness and fear of dying (Pierce et al, 2020;Rajkumar, 2020). A study conducted during the recent COVID-19 pandemic found a 6to 7-fold increase in symptoms of depression and anxiety in adults (Feter et al, 2020). A recently published global review found female gender, unemployment, student status and people with chronic/psychiatric disorders as risk factors that could deteriorate the mental health of people during COVID-19 outbreak (Xiong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Описание исследования, нацеленного на выяснение особенностей динамики депрессии и тревоги среди взрослых бразильцев во время пандемии COVID-19, приводят Фетер Н. (Feter N.) с коллегами [19]. Это первое исследование, в ходе которого изучалось влияние пандемии COVID-19 на проблемы психического здоровья в Бразилии.…”
unclassified